KELOMPOK KEPENTINGAN DALAM PROSES POLITIK PEMERINTAHAN DI DAERAH STUDI KASUS PERSATUAN GURU REPUBLIK INDONESIA KOTA PEKANBARU ( PERIODE 2008 – 2013 ) - MUSLIYANDI "; HASANUDDI " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Republic of indonesia teacher coalitions (pgri) sebanar have been there sincebeginning bew order time has stood until now yangn more mencitra in the world ofeducation. so that not amazing pgri this always has member increasing enoughsignificant every year it. with total mass manyoritas teacher and this lecturer pgrithis success so that from success researcher that is: how does city republic ofindonesia teacher coalitions activity/implementation pekanbaru in memperjuangmember importance? , and everything factor haves city republic of indonesia teachercoalitions pekanbaru in memperjuang the member importance? .This watchfulness aim realizes activity/implementation pgri city pekanbaru inmemperjuang member importance and factor haves pgri city pekanbaru inmemperjuang the member importance. this watchfulness use upon which for pgri citypekanbaru in runs function and the character to the fore so that better. watchfulnesslocation bertempat at city pekanbaru that is in board pgri city pekanbaru, regionparliament office (dprd) city pekanbaru and city education official pekanbaru. thiswatchfulness kind qualitative watchfulness with descriptive method. in researcherdata collecting uses interview technique, observation and documentation. by usingkey informant as information source about this watchfulness.Based on watchfulness result in skripsi this, inferential that pgri pekanbaru inrun function and the task more emphasized articulation to government, drpdpekanbaru, and policies party passes hungan personal and nearness pgri pekanbaruitself to former the member. with total mass many pgri pekanbaru can pass bydemocracy filter to laid the representation at dprd pekanbaru and policies partyKeywords: importance group, policies process, importance articulation